The new capitalism - Halal, William E. (Wiley, 1966)
An incisive look at American business in transition. Examines the new course being charted by companies both large (such as IBM and TRW) and small (such as Microsoft and Genentech). Integrates a range of data, trends, and opinions of what the future will look like and how to prepare for it. Topics include soft growth, participative leadership, creative enterprise, economic community, and democratic free enterprise.